Pengaruh Kepuasan Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan Bagian Perbendaharaan dan Mobilisasi Dana RSUP Dr Sardjito - Tutuk Wahyu Widodo (JURNAL EKOBIS DEWANTARA, 2018)
ABSTRACT The purpose of this study is to describe (1) the effect of job satisfaction variable on employee performance, (2) the effect of work environment variable on employee performance, and (3) the influence of job satisfaction variable and work environment together to employee performance at Treasury and Fund Mobilization Division of Dr Sardjito Yogyakarta General Hospital. This study uses quantitative approach with causal associative research category, with the population of all employees of Treasury and Fund Mobilization Division Dr. Sardjito General Hospital, with 40 people who are participate as research samples. Data collection methods used questionnaires, while data analysis techniques used simple linear regression analysis analysis supported by F (F-test) and T (T-test) test and classical assumption test consisting of multicolinearity test, normality test and heteroscedasticity test. Based on the results of the analysis shows that job satisfaction has a positive and significant effect on the employee's performance on " Treasury and Fund Mobilization Division of Dr Sardjito General Hospital", proven with t-count value greater than t-table (4,082> 1,687), with probability value (0,000) smaller than the significant 0.05 level. The work environment has a positive and significant effect on the employee's performance on " Treasury and Funds Mobilization Division of Sardjito General Hospital", as evidenced by the larger t-count value of t-table (3.661> 1.687), with the probability value (0,000) smaller than the significant level 0.05. Job satisfaction and work environment together have a positive and significant effect on the performance of employees "Treasury and Fund Mobilization Division of Dr Sardjito General Hospital", proved by the value of F-count larger than F-table (376.648> 3.24) with a significant value of 0.000, smaller than the significant level of 0.05. Coefficient of Determination of 32.5%, which means job satisfaction and work environment can affect the amount of 32.5% performance and the rest influenced other variables that do not exist in this study of 67.5%. Keywords: Job Satisfaction, Work Environment, Performance